Effects of weed control on survival and early growth of Pinus ponderosa plantations in Patagonia, Argentina - Davel, Miguel; Tejera, Luis; Honorato, Martín; Sepúlveda, Eduardo (Bosque (Valdivia), 2006)
Pinus ponderosa is the tree species with the highest potential for plantation in the Andean Patagonian Region of Argentina. Today, most of these plantations are carried out without any site preparation nor taking into account the relationship site-type of seedling. In this study we present the results of three plantation trials carried out in three different sites (regarding precipitation regime and vegetational characteristics), by using two types of seedlings, and with and without herbicide weed control. The period analyzed corresponds to 6 years after trial installation. A differential response was found among types of plant growing in the different sites, and an increase in establishment and growth was registered for those plants grown in weed-free areas when compared to the untreated controls. It was also shown that the herbicide effect upon plant growth starts appearing the second year after treatment.